Liquid waste treatment containing Rhodamine B using emulsion liquid membrane from waste cooking oil - Herry Purnama; Dina Ekariana Dewi; Nabilah Miftachul Jannah; Azzahra Ardya Kamaratih; Nur Hidayati (Results in Engineering)
Dye pollutants in water, particularly Rhodamine B, poses significant environmental and health risks due to its toxicity and persistence in aquatic ecosystems. This study explores the use of waste cooking oil (WCO) as a sustainable organic phase in the emulsion liquid membrane (ELM) technique to extract Rhodamine B from wastewater. WCO offers advantages as a non-toxic, non-flammable, and accessible solvent that reduces secondary pollution and costs. Key parameters, including surfactant concentration, carrier substance, feed concentration, and phase volume ratios, were systematically optimized to enhance extraction efficiency and membrane stability. The improved ELM method achieved a maximum dye removal efficiency of 95 %, with membrane breakage consistently maintained below 19 %. These findings suggest that WCO-based ELM is an effective and environmentally friendly alternative for dye removal, supporting sustainable wastewater treatment and contributing to pollution reduction.